2017
DOI: 10.3390/en10071003
|View full text |Cite
|
Sign up to set email alerts
|

Prediction in Photovoltaic Power by Neural Networks

Abstract: Abstract:The ability to forecast the power produced by renewable energy plants in the short and middle term is a key issue to allow a high-level penetration of the distributed generation into the grid infrastructure. Forecasting energy production is mandatory for dispatching and distribution issues, at the transmission system operator level, as well as the electrical distributor and power system operator levels. In this paper, we present three techniques based on neural and fuzzy neural networks, namely the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Prior to deep learning and LSTM networks, the literature has been filled by statistical and data driven modeling tools where the univariate approach represented by (2) or (3) has been pursued by solving prediction through data regression. In machine learning, both recurrent and feed-forward models have been investigated by using shallow neural networks, possibly hybridized with fuzzy modeling and evolutionary computing for complex optimization [14], [37]. There are two main groups of forecasting approaches in the considered field: indirect and direct [38].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to deep learning and LSTM networks, the literature has been filled by statistical and data driven modeling tools where the univariate approach represented by (2) or (3) has been pursued by solving prediction through data regression. In machine learning, both recurrent and feed-forward models have been investigated by using shallow neural networks, possibly hybridized with fuzzy modeling and evolutionary computing for complex optimization [14], [37]. There are two main groups of forecasting approaches in the considered field: indirect and direct [38].…”
Section: Related Workmentioning
confidence: 99%
“…This is the reason why the prediction of power output has become a necessary tool for all the actors involved [14]: producers need predictions to prepare their respective offer strategies; consumers need predictions to maximize their profit; Transmission (TSO) and Distribution (DSO) System Operators need predictions to optimize short and medium term decisions for energy regulation and dispatching. Furthermore, an accurate prediction system, which is the key element within automatic modeling tools for data analytics and intelligent operation control, may enable prosumeroriented home energy management systems [15] and reduce both energy and operation costs.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the two and introducing scaling factors and translation factors can improve the generalization ability and convergence speed of the network. It has a more flexible function fitting efficiency (Rosato et al 2017). However, the initial weights and wavelet factors of the wavelet neural network are randomly generated.…”
Section: Optimized Wnn By Cuckoo Search Algorithmmentioning
confidence: 99%
“…Xu et al [21] developed a method for day-ahead prediction and shaping of the dynamic response of the demand at bulk supply points without field measurements, broadly based on the application of the artificial neural network, Monte Carlo simulations, and load modeling approaches. Rosato et al [22] proposed a new approach based on neural and fuzzy neural networks for PV power prediction, and the forecasting results in the training of neural networks confirm such a trend for which the performance decreases progressively as the length of the training set increases because the training process is more difficult. Dolara et al [23] proposed the hybrid method, combining an artificial intelligence technique with an analytical physical model, and the results showed that the length training set is critical to the dynamic characteristics of neural networks.…”
Section: Introductionmentioning
confidence: 98%